(3QSGdI GdMOhOs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hGdUdGI Ydi eMeO hGdg hHYO aEf GUObGFi SCdhfi Cf Cedi Ydjge MOhOkG TJG aWGdHhfi HJMOjOgG aGSJZajJ ef Pdc YdekG HGfg cGdCeQ GdeJYOO Ydi GdHTQ ShGAkG cGf JMOjOkG Ch QSekG s
(3BNQgG (B:s
(3hGdHYO GdPi Hjf GdNWjf GdePchQjf gh YQV hdjS SWM hEf cGf cd NW PG Whd hcd SWM PG YQV hbO fLR YQVfG ef cJGH GdLO bGfhfkG hJaUjdkG hGddg GdgGOi Edi GdUhGH hEdjg GdeQLY hGdeBH Je cJGH GdMOhO ddEeGe GdaGVd GdeMbb GdZRGdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B861s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(3949) s
Keywords: (3GdadSaI hGdefWbs